A COMPARATIVE STUDY OF PROBLEMATIC INTERNET USE AND LONELINESS AMONG TURKISH AND KOREAN PROSPECTIVE TEACHERS - (:unkn) unknown (TURKISH ONLINE JOURNAL EDUCATIONAL TECH-TOJET, 2011)
The main aim of this study is to compare the problematic internet use and its relation to loneliness among two nations' prospective teachers, Turkey and South Korea. Five hundred and ninety five prospective teachers from three universities, two from Turkey and one from South Korea participated in the study. Generalized Problematic Internet Use Scale 2 and UCLA Loneliness Scale were used to collect data. Some of the major findings are as follows: a) No differences were found between the problematic Internet use of Turkish and Korean prospective teachers; b) Male Turkish prospective teachers found to have more problematic use of internet than female counterparts on the other hand no differences were found among South Korean prospective teachers by means of sex; c) Positive but low correlations between problematic Internet use and loneliness levels of prospective teachers of both nations; d) There is a significant difference between Turkish and Korean prospective teachers. South Korean prospective teachers were found to be in higher levels of loneliness than Turkish counterparts.
Keywords: Problematic internet use; internet addiction; prospective teachers; comparative study; COLLEGE-STUDENTS; SCALE; VALIDITY; MODEL